To Study the Correlation Between Chronic Upper Back Pain and Shoulder Joint Propriocepton In Under Graduate Students - Tejani, Neelam; Patil, Swaroop; Rayjade, Amrutkuvar; Sharma, Seema; Rathod, Sagar (Journal of Neonatal Surgery, 2025)
Background Musculoskeletal pain is a prevalent issue among young adults, with neck, shoulder, and upper back pain being commonly reported in college students. Contributing factors include carrying heavy bags, prolonged studying hours, sustained abnormal postures during lectures, and extended use of mobile devices in improper positions (e.g., complete neck flexion, slouched shoulder posture) while sitting unsupported. Objectives This study aimed to assess chronic upper back pain using the Numeric Pain Rating Scale (NPRS) and altered proprioception in undergraduate students. Materials and Methods A total of 69 undergraduate students experiencing chronic upper back pain were recruited for this study. Pre- and post-assessments were conducted to measure changes in pain and shoulder joint proprioception. Pain intensity was subjectively assessed using the Numeric Pain Rating Scale (NPRS), where participants selected a number corresponding to their pain level. Shoulder joint proprioception and range of motion (ROM) were measured using a goniometer. The ROM was evaluated for flexion, extension, abduction during both eyes open and eyes closed phases. Results The analysis revealed that undergraduate students with chronic upper back pain demonstrated reduced shoulder joint range of motion (ROM) Closed eyes , which significantly showed a difference in their proprioception. Difference was as follows: Flexion: Open eyes :150, Close eyes :120, Extension: Open eyes : 50° ,Close eyes : 40°, Abduction: Open eyes : 135°, Close eyes : 110°. Conclusion The study concludes that undergraduate students with chronic upper back pain exhibit significantly altered shoulder joint proprioception.